Short-notice (48 hours) ACCREDITATION trial in Australia: stakeholder perception of assessment thoroughness, resource requirements and workforce engagement - Hailie Uren; Branislav Vidakovic; Michael Daly; Kellie Sosnowski; Vladimir Matus (BMJ Open Quality)
Background External, independent accreditation assessments of healthcare organisations are necessary to ensure the nationally legislated minimum standards of quality and safety (QS) are met. The predetermined scheduling of the assessments continues to be criticised due to the high level of organisational emphasis on preparing for accreditation.Objectives To determine the stakeholder perception of assessment thoroughness, staff resource requirements and workforce engagement changes if only 48 hours’ notice is given to an organisation prior to an accreditation assessment, compared with the standard-notice accreditation process.Methods Logan and Beaudesert Hospitals in Brisbane, Australia, trialled the ‘Short-Notice Survey Accreditation Assessment Process’ (SNAAP) between August 2017 and December 2018. The organisation was given just 48 hours’ notice prior to an accreditation assessment. Staff perception of the standard-notice accreditation process and short-notice process was assessed using a 5-point Likert scale repeated measures questionnaire (pretrial, 6 and 12 months after SNAAP launch).Results There was a statistically significant stakeholder opinion that SNAAP more effectively identified the true strengths and achievements of the organisation’s QS compared with ‘standard-notice’ survey (p=0.033). There was a significantly lower overall perceived proportion of staff resources required for SNAAP preparation in contrast to ‘standard-notice’ process (Baseline Av=21.38% vs Follow-up 1 and 2 Av=9.75%–6.25%, p=0.021). The questionnaire results reflected that SNAAP increased staff engagement in QS activities (Av=3.75 and 3.69, 95% CI=3.45–4.05 and 3.45–3.94).Conclusions With sufficient cultural and operational preparation to move to SNAAP, hospitals can potentially use SNAAP as a truer validation of QS standards, require less staffing resources to prepare for accreditation assessments and improve staff engagement in QS assurance and improvement.